Pengalaman Pembelajaran Daring Pada Penggunaan Whatsapp Bagi Mahasiswa Uin-Su Di Era Pandemi Covid-19 - Nunzairina Nunzairina (BEST Journal (Biology Education, Sains and Technology), 2022)
This study aims to determine the use of WhatsApp which is used by students of the State Islamic University of North Sumatra in conducting online learning, then to find out the obstacles of online learning to students of the State Islamic University of North Sumatra and to find out how to solve the obstacles of lectures via WhatsApp. This type of research is comparative research, namely comparison. The population in this study were all students of Communication Studies semester IV Stambuk 2019 totaling 179 students. The selection of research samples was determined by randomly selecting two classes or random sampling. This study uses a quantitative approach and uses an online survey in the form of a google form to collect the necessary data or information. The results show that the effect of online learning via WhatsApp is in a good category based on the average value of the percentage of learning via WhatsApp obtained with a percentage value (67.8 %). Then the results of the study of the sub-variable of the effect of using WhatsApp on affective behavior obtained an average score of 72.5%, namely in the statement "WhatsApp is a medium that is often used by students for online learning, while the effect of using WhatsApp on cognitive behavior is 32.5% was obtained from the statement of learning methods through WhatsApp which made it easier for students to repeat learning and also 25% of the highest score was obtained from the statement of student learning with the WhatsApp method, which greatly facilitated student understanding.